HUMANIZAÇÃO NO PARTO E AS VIVÊNCIAS DE MULHERES EM UMA INSTITUIÇÃO DE ENSINO - Frias, Luzinéa de Maria Pastor Santos (2013)
The childbirth humanization as a movement searches for changes on the childbirth attention practices, discussing among other questions the abusive use of technology and the woman space in childbirth scene. As a public policy intends to ensure the access to assistance to childbirth in the services of the health unique system (HUS/SUS) and improve the maternal health indicators and neonatal. This study had as goal: Analyze the meaning of the humanization actions proposed by the Childbirth Humanization Program and Birthing in the Materno Infantil Hospital in São Luís-MA, having as empirical support speeches of women about the lived experience in the childbirth and of institutional leaders about the viability of the process of humanization in the maternity. Therefore, was made a qualitative approach research that used the focus group techniques with 28(twenty-eight) women in postpartum period and a semi structured interview with 5(five) female managers of the institution. The material analysis was made through the content analysis technique, showed the following categories: the violence on childbirth assistance and childbirth humanization and their meanings. Data revealed that women lived childbirth as an violent event, which have reveled the search for a bed, devaluation of the partum pain, exam s recurrence and companion s restrictions. The users mean the humanization as an ambience, presence of the father in the partum and the right to cesarean. To the responsible the humanization means the decrease of pain through anesthesia, be empathic and take care of the caregiver. Companion s unpreparedness and lack of professional s evolvement were the main boundaries to humanization and the physical structure and professional ability were advantages. Centralized management, insufficiently participation in decision-making by users and servers, institutional violence in childbirth practices, becomes conflicting and contradictious, besides an obstacle to reach a humanized childbirth attendance at the studied maternity.